The Indo-European Voice of Barbarians - Bâgiu, Lucian Vasile; Bâgiu, Paraschiva (Swedish Journal of Romanian Studies, 2018)
In our essay we shall focus on the analyses (cum grano salis) of a limited number of words from the introductory pages of the novel Barbarians (such as gorgan, grui, crăpcean, fală, sfadă, etc.). Here, more than elsewhere the author makes use of a good amount of rather strange words (old, regional or folk) in his stylistic attempt to conceive the realm of the Dacians. We shall make an analysis of the etymology of these rather uncommon words as designated in Vinereanu's Etymological Dictionary of Romanian Language (2008) (unlike the traditional Romanian dictionaries, a different vision). From the (probable) linguistic discrepancies and stylistic preferences, findings will be drawn and novelties will be suggested, concerned with Romanian language and culture.